PERFORMANCE SIMULATION ON THE SHELL AND TUBE OF HEAT EXCHANGER BY ASPEN HYSYS V.10 - Erlinda Ningsih; Isa Albanna; Aita Pudji Witari; Gistanya Lindar Anggraini (Jurnal Rekayasa Mesin, 2022)
Heat exchanger type shell and tube, which is the most commonly used heat exchanger in various industries. The efficiency of heat exchangers can be seen from their performance to affect its economy from a process. The purpose is to determine the influence of the hot fluid flow rate and the cold fluid on the overall heat transfer coefficient (U) and log mean temperature difference (ΔTLMTD) values. This simulation is done using Aspen HYSYS V.10 applications and obtained data of the total heat transfer coefficient (U) and ΔTLMTD values. The heat exchanger shell and tube used type 1-2 with single segment type 4 baffle, triangular tube layout, and shell length 1000mm. This simulation results in a hot fluid flow rate compared to reverse with the overall heat transfer coefficient and a cold fluid relative to the overall heat transfer coefficient, with the two best fluid flow rates at 2100 kg/h hot fluid and 1800 kg/h cold fluid at 10400 Kj/oC.h. The influence of the hot fluid flow rate on ΔTLMTD is relative to the straight, while the cold fluid flow rate is relative to the reverse, with the value of the second-best fluid flow rate at the 2100 kg/h hot fluid and the 1800 kg/h cold fluid at 26.25oC